2021
DOI: 10.1177/15347354211021920
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Radiosensitizing Effects of Zinc Oxide-Caffeic Acid Nanoparticles against Solid Ehrlich Carcinoma in Female Mice

Abstract: This study aimed to evaluate the anticancer and radio-sensitizing efficacy of Zinc Oxide-Caffeic Acid Nanoparticles (ZnO-CA NPs). ZnO-CA NPs were formulated by the conjugation of Zinc Oxide nanoparticles (ZnO NPs) with caffeic acid (CA) that were characterized by Fourier Transform Infrared Spectra (FT-IR), X-ray Diffractometer (XRD), and Transmission Electron Microscopy (TEM). In vitro anticancer potential of ZnO-CA NPs was evaluated by assessing cell viability in the human breast (MCF-7) and hepatocellular (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 110 publications
(146 reference statements)
1
5
0
Order By: Relevance
“…While biosynthesized ZnO NPs were effective on the proliferation of the breast cancer (MCF7) cells with IC 50 61.92µM compared with 248.72µM for chemically synthesized ZnO NPs, (Fig. 7B and D) which in agreement with Sayed et al [41] who discovered that dose-dependent effects were observed MCF7 and HepG2 cancer cells treated with varied dosages of ZnO NPs had a decrease in viability and a steady increase in toxicity. Because of this, "green" or biosynthesized nanoparticles (NPs) exhibit greater stability and activity than NPs made using more traditional methods [42].…”
Section: Cytotoxicity Assay Of Zno Nps Using (Mtt) Assay Protocolsupporting
confidence: 88%
“…While biosynthesized ZnO NPs were effective on the proliferation of the breast cancer (MCF7) cells with IC 50 61.92µM compared with 248.72µM for chemically synthesized ZnO NPs, (Fig. 7B and D) which in agreement with Sayed et al [41] who discovered that dose-dependent effects were observed MCF7 and HepG2 cancer cells treated with varied dosages of ZnO NPs had a decrease in viability and a steady increase in toxicity. Because of this, "green" or biosynthesized nanoparticles (NPs) exhibit greater stability and activity than NPs made using more traditional methods [42].…”
Section: Cytotoxicity Assay Of Zno Nps Using (Mtt) Assay Protocolsupporting
confidence: 88%
“…Plant-derived natural products have incredible potential to control cancer cell growth . Previous studies confirmed that the ASLE contained flavonoids, alkaloids, saponins, tannins, glycosides, steroids, phenols, and various acetogenin compounds and demonstrated a various array of pharmacological activities involving antioxidant, anti-cancer, and anti-inflammatory properties. , Nowadays, plants are performing a remarkable role in nanoparticle synthesis . To ameliorate cancer therapeutic protocols, the current study was implemented to determine the antitumor efficacy and hepato-renal protective effect of ASLELN against Erhlich Ascites Carcinoma (EAC) in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Nowadays, plants are performing a remarkable role in nanoparticle synthesis. 19 To ameliorate cancer therapeutic protocols, the current study was implemented to determine the antitumor efficacy and hepato-renal protective effect of ASLELN against Erhlich Ascites Carcinoma (EAC) in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The ZnO NPs’ antioxidant potential was also confirmed through the continual reduction of zinc ions. The ZnO NPs were proven to be effective in the treatment of UTIs and fungi infections and, even further, showed great antitumor action [ 167 , 168 ]. Due to these particular advantages, it would be worthwhile to pursue further research of its properties and applications in industries such as food processing, pharmaceuticals, and cosmetics, in which the ZnO NPs could have a positive impact [ 160 , 169 , 170 ].…”
Section: Nanotechnology Used As a Diagnostic Methods And In Antimicro...mentioning
confidence: 99%